Asynchronous Learning Model (Its Implementation Via Google Classroom) - Oktari Sela; Fadly Azhar; Udi Samanhudi (ELT-Lectura, 2022)
The paper aims to explore how the students’ perception on the implementation of the asynchronous learning model via google classroom and the process of its implementation by the teachers. In this research, students’ perception on the implementation of the asynchronous learning model via google classroom is conceptualized by five categories: the development of students' self-control towards their learning or being independent, development of self-reflection on students' learning, convenience (no presence needed), fewer social obstacles (for introverted students), awareness in using technology and interactivity regardless of the time and place constraints. Meanwhile, the process of its implementation is set by three components, they are uploading the material, asking the students to learn the materials and doing a task, and giving feedback. 96 students from SMPN 1 Tembilahan participated in answering the questionnaire sheet and three teachers were responding to the interview. The results showed that students’ perception on the implementation of the asynchronous learning model via google classroom is good because most of them claimed that the implementation of Google Classroom by using an asynchronous model gives a positive impact on them, especially for being more independent, being aware of using technology, and being more responsible in doing tasks. Then for the process of its implementation, all three teachers followed the three components above and they improve it creatively